Repositioning Engaged Anthropology: Critical Reflexivity and Overcoming Dichotomies - Larsen, Peter; Bacalzo, Doris; Naef, Patrick; Elif Tibet, Eda; Baracchini, Leïla; Riva, Susie (Swiss Journal of Sociocultural Anthropology, 2022)
This special issue aims to shed light on and recognize the full potential of engaged anthropology and its place in academia and beyond. It argues for an inclusive approach to be both theoretically enriching and methodologically grounded in diverse practices and forms. The introduction addresses common confusions and obstacles distracting engaged anthropology from its core premises and potentials. As the Interface Commission of the Swiss Anthropological Association (SEG), we seek to deepen the conversation about how engagement bolsters the discipline to stay relevant and robust, and embark on new paths of theoretical reflection. By “repositioning” engaged anthropology at the heart of contemporary anthropology, we seek to overcome unproductive dichotomies on engagements and practices by embracing critical reflexivity in the process of knowledge production and social action.